An Intelligent Fuzzy Based Technique of Making Food Using Rice Cooker - Chandra Pradhan, Mohan (Asian Journal of Electrical Sciences, 2016)
This paper aims at presenting the idea of controlling the cooking time of rice based on the type of rice and quantity of water using fuzzy logic control. The paper describes the procedure that can be used to get a suitable cooking time for different types of rice. The process is based entirely on the principle of taking non-precise inputs from the sensors, subjecting them to fuzzy arithmetic and obtaining a crisp value of the cooking time. It is quite clear from the paper itself that this method can be used in practice to further automate the rice cookers. Nevertheless, this method, though with much larger number of input parameters and further complex situations, is being used by the giants like LG and Samsung.The rice cooker features with advanced logic technology, which allows it to think for itself and make adjustments to the temperature and timing of batch of rice totally on the cooking. A spherical inner cooking pan and heating system distributes heat evenly so the rice at the bottom is the same consistency.